The Effect of Working Hours on Health - Iéns Berniell; Jan Bietenbeck (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2017)
Does working time causally affect workers' health? We study this question in the context of a French reform which reduced the standard workweek from 39 to 35 hours, at constant earnings. Our empirical analysis exploits variation in the adoption of this shorter workweek across employers, which is mainly driven by institutional features of the reform and thus arguably exogenous to workers' health. Difference-in-differences and lagged dependent variable regressions reveal a positive effect of working hours on smoking and a negative effect on self-reported health. Results are robust to accounting for endogenous job mobility and differ by workers' occupations.
Keywords: I10; I12; J22; 330; Working Hours; Health; Smoking; BMI